Light intensity and photoperiod interact to alter the phytonutrient profile and light-use efficiency of mizuna grown for the space diet - Ethan W. Darby; Sarah P. Armstrong; Gioia D. Massa; Kellie J. Walters (Scientific Reports)
Abstract Beyond mere caloric intake, the nutritional quality of food will be key to maintaining astronaut health during exploration-length missions. The production of leafy greens aboard spacecraft can help to provide consistent daily nutrition; however, maximizing the nutritional yield of each plant will be key to sustainable and efficient dietary supplementation. Brassica rapa ssp. nipposinica ‘Red Hybrid’ was grown under environmental conditions similar to those of the International Space Station and the effect of light intensity and photoperiod on nutritional and biomass yields were evaluated. Four light intensities (200, 400, 600, and 800 µmol·m− 2·s− 1) applied over a 16- or 24-h photoperiod were implemented and the resulting concentrations of ascorbic acid, thiamine, phylloquinone, β-carotene, lutein, zeaxanthin, total anthocyanins, calcium, potassium, magnesium, and iron were quantified. The 800 µmol·m− 2·s− 1 by 16-h treatment produced the best nutritional profile for supplementing the astronaut diet, offering the following percentages of recommended daily intake per 75 g serving: 100% phylloquinone, 63% ascorbic acid, 2.7% thiamine, and 97% retinol (as β-carotene precursor). However, when evaluated for light use efficiency (yield·MJ− 1), the 200 µmol·m− 2·s− 1 treatments (16- and 24-h) were found to perform better, yielding more mass and phytonutrients per MJ of energy utilized.